Numerical simulation of embryo transfer: how the viscosity of transferred medium affects the transport of embryos - Ding, Dali (Theor Biol Med Model, 2018)
BACKGROUND: Embryo transfer (ET) is a key step of assisted reproductive procedures, where the transferred medium containing the embryos is injected into the uterine cavity through a transcervical catheter and blended with intrauterine fluid in the uterine cavity. This procedure determines the delivery sites of embryos in the uterine cavity and has crucial impact on the implantation. Due to practical restrictions and ethical issues, it is often difficult to perform an in vivo study in humans to examine factors that affect the motions and delivery of embryos during ET. Alternatively, mathematical modeling is a powerful tool to that end. RESULTS: A computational model is developed to simulate the intrauterine mixing flow and track the embryo motions. Two important factors affecting the intrauterine flow are studied via this model: the viscosity of the transferred medium and the injection speed. Numerical results show that the dispersion pattern and the final delivery sites of the embryos are significantly influenced by the viscosity of the transferred medium. Specially, increasing the transferred medium viscosity close to that of the uterine fluid can enhance the probability that the embryos are delivered close to the fundus and keep them from being dragged backward to the cervix during catheter withdrawal. In addition, a slow injection speed can lower the driving force on the embryo during ET, which can prevent the embryo from being injured. CONCLUSIONS: Based on our study, the practice of using a transferred medium with similar viscosity to that of the uterine fluid and a slow injection speed is recommended for real embryo transfer procedures in clinic.